Tra Firenze e Roma: modelli danteschi - Ferroni, Giulio (Firenze Architettura, 2021)
For Dante, Florence is the root and the form of a personal identity that has become the sign of corruption and the negation of the human. In opposition to it is Rome, the center of measure and control of a pacified world, a city ordered by God. In any event, Dante’s gaze would never cease, in a series of connections involving both identification and distancing, to turn towards the city of his birth: an invitation not to forgo, in our contemporary cities, the possibility of maintaining a vital balance between past and future.